2017
DOI: 10.1167/17.9.13
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic position uncertainty impairs overt search performance

Abstract: Uncertainty regarding the position of the search target is a fundamental component of visual search. However, due to perceptual limitations of the human visual system, this uncertainty can arise from intrinsic, as well as extrinsic, sources. The current study sought to characterize the role of intrinsic position uncertainty (IPU) in overt visual search and to determine whether it significantly limits human search performance. After completing a preliminary detection experiment to characterize sensitivity as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Regardless of whether it is extrinsic or intrinsic, position uncertainty impairs performance for detecting, discriminating, and localizing stimuli. This is indicated by decreases in detection and localization accuracy (Burgess & Ghandeharian, 1984;Eckstein, Thomas, effects of position uncertainty seem to persist in search tasks requiring eye movements (i.e., overt search tasks; Semizer & Michel, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Regardless of whether it is extrinsic or intrinsic, position uncertainty impairs performance for detecting, discriminating, and localizing stimuli. This is indicated by decreases in detection and localization accuracy (Burgess & Ghandeharian, 1984;Eckstein, Thomas, effects of position uncertainty seem to persist in search tasks requiring eye movements (i.e., overt search tasks; Semizer & Michel, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, its effect on performance can be observed by manipulating the visual environment. In a recent study, Semizer and Michel (2017) introduced an experimental technique that modulates the effects of intrinsic uncertainty independently of extrinsic uncertainty by manipulating the distribution of clutter in synthetic noise displays. Using this technique, the authors showed that intrinsic position uncertainty substantially limits overt search performance and that its effects are especially evident when the amount of extrinsic uncertainty is controlled.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations